STCR based nutrient management in soybean (Glycine max) for higher productivity and profitability - RAGHAV, RANJEET SINGH; SINGH, Y V; KUMAR, MUKUL; DEY, PRADIP; DUBEY, S (The Indian Journal of Agricultural Sciences, 2019)
Farmer’ Participatory On Farm Trials (FP-OFT) were conducted at 10 different locations in Raisen district of Madhya Pradesh during two consecutive years of kharif 2015–16 in medium black soils to study the influence of soil test crop response (STCR) approach vis-a-vis farmers’ practice on productivity and economics of soybean [Glycine max (L.) Merr.]. Result revealed that targeted seed yield of soybean (1500 kg/ha) was achieved by adoption of STCR approach. The mean percentages of increase in grain and Stover yields of soybean under STCR were 46.7% and 46.9%, respectively over the farmers’ practice (FP). The plant height, number of root nodules, pods/plant and test weight of seed increased by 11.5%, 11.1%, 29.1% and 24.0%, respectively over the farmers’ practice. There was much larger negative balance in available nitrogen and available potassium levels under farmers’ practice compared to STCR. The economic parameters of crop i.e. gross return, net returns and benefit-cost ratio (BCR) under the STCR approach were between ` 34100–38662.5/ ha, ` 16566–21462/ ha and ` 0.89–1.60 which were higher as compared to farmers’ practice across the locations. STCR approach must be adopted by the farmers for higher crop productivity, profitability and soil nutrient balance.